The Predictors of Caregiver’s Burden and Depression Level in Caring Elderly People with Dementia at Community - Yossie Susanti Eka Putri; Ni Made Riasmini (Universitas Airlangga, 2013)
Introduction: Most older people with dementia in Indonesia stay at home, cared by family members. Family caregivers even experience physical, psychological, social, and fi nancial problems. Care giving demands often lead to caregiver burden and depression. The objective of this study was to determine factors which contribute burden and depression experienced by the caregivers of older people with dementia.Method: Design was descriptive analytic with cross sectional approach. The population were caregivers living with older people with dementia. Sample size were 183 respondents. The independent variables were caregiver’s contextual factors, stressor caregiving, and intervening factor. The dependent variables were the burden of care and level of caregivers’ depression. Data were collected using questionnaire. Data were analyzed using linier regresion.Results: Statistical analyses showed marital status was significantly related to caregivers’ burden. While worked, education, and relationships with older people were significantly related with caregivers’ depression level. Memory and behavior problem, the task of caring and satisfaction of caring were related with caregivers’ burden and depression level. Multivariate analyses show health status was the most factors related to caregivers’ depression level. Memory and behavior problems was main factor related to caregivers’ burden of caring for older people with dementia.Conclusion: The results are expected to provide information about the extent of caregivers’ burden and depression which experienced in care giving, therefore the services can be designed based on the needs of the caregivers of persons with dementia in the community.